Endothelial-to-mesenchymal transition drives atherosclerosis progression - Chen, Pei-Yu; Qin, Lingfeng; Baeyens, Nicolas; Li, Guangxin; Afolabi, Titilayo; Budatha, Madhusudhan; Tellides, George; Schwartz, Martin A.; Simons, Michael (The Journal of clinical investigation, 2015)
The molecular mechanisms responsible for the development and progression of atherosclerotic lesions have not been fully established. Here, we investigated the role played by endothelial-to-mesenchymal transition (EndMT) and its key regulator FGF receptor 1 (FGFR1) in atherosclerosis. In cultured human endothelial cells, both inflammatory cytokines and oscillatory shear stress reduced endothelial FGFR1 expression and activated TGF-β signaling. We further explored the link between disrupted FGF endothelial signaling and progression of atherosclerosis by introducing endothelial-specific deletion of FGF receptor substrate 2 α (Frs2a) in atherosclerotic (Apoe(-/-)) mice. When placed on a high-fat diet, these double-knockout mice developed atherosclerosis at a much earlier time point compared with that their Apoe(-/-) counterparts, eventually demonstrating an 84% increase in total plaque burden. Moreover, these animals exhibited extensive development of EndMT, deposition of fibronectin, and increased neointima formation. Additionally, we conducted a molecular and morphometric examination of left main coronary arteries from 43 patients with various levels of coronary disease to assess the clinical relevance of these findings. The extent of coronary atherosclerosis in this patient set strongly correlated with loss of endothelial FGFR1 expression, activation of endothelial TGF-β signaling, and the extent of EndMT. These data demonstrate a link between loss of protective endothelial FGFR signaling, development of EndMT, and progression of atherosclerosis.